INOVASI KURIKULUM DAN TEKNOLOGI PEMBELAJARAN (DEEP LEARNING) - Haditsa Qur'ani Nurhakim; Isnan, Isnan Rojibillah; Harsing, Harsing; Supiana, Supiana; Qiqi , Qiqi Yuliati Zakiah (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2025)
The deep learning instructional model, as proposed by Abdul Mu’ti, emphasizes mindful, meaningful, and enjoyable learning experiences. This approach not only encourages students to memorize but also to deeply understand and internalize knowledge, thereby enhancing critical thinking, independence, and active engagement in the learning process. This study aims to examine the implementation of the deep learning model in primary and secondary education in Indonesia through a literature review method. Based on an analysis of various academic sources and recent educational policies, it was found that this model holds significant potential for improving learning quality and fostering a more reflective and collaborative learning environment. However, its implementation still faces several challenges, including limited infrastructure, insufficient teacher training, and the dominance of traditional curricula that restrict learning flexibility. This article recommends strengthening teacher capacity through continuous professional development, providing adequate facilities and infrastructure, and developing policies that support the adoption of deep learning approaches. With the right support, deep learning can become a strategic educational approach to enhance the quality of education in Indonesia and to shape a generation that is adaptive and competitive in the global era.